Two new desma-less species of Theonella Gray, 1868 (Demospongiae: Astrophorida: Theonellidae), from the Great Barrier Reef, Australia,and a re-evaluation of one species assigned previously to Dercitus Gray, 1867 - Hall, Kathryn A.; Ekins, Merrick G.; Hooper, John N.a. (Zootaxa, 2014)
Extensive surveys of the biodiversity on the seafloor of the inter-reef regions of the Great Barrier Reef, Australia, have resulted in the collection of large numbers of sponges, many of which are likely new to science. Identification of these sponges, however, was made difficult by the absence in some specimens of key diagnostic characters, such as megascleres. We used an integrated approach to the taxonomy of these sponges, incorporating morphological examination by SEM, analysis of DNA sequence data (using the COI barcoding fragment of mtDNA) and preliminary studies of the chemistry of the sponges, to describe the new species, which were found to contain no native spicules other than acanthose microrhabds. Here, we propose two new species of Theonella Gray, 1868: Theonella deliqua n. sp. (found in association with a single unidentified species of siliquariid mollusc) and Theonella maricae n. sp. from the Great Barrier Reef. Further, we propose the new combination of Theonella xantha (Sutcliffe, Hooper and Pitcher 2010) n. comb. for another microrhabd-only-bearing species. On the basis of our gene trees, we recognise Theonella (and Theonellidae Lendenfeld, 1903) within Astrophorida Sollas, 1887. We discuss the potential for chemotaxonomic and DNA-based insights into the origins and radiation of species of Theonella and explore the evolutionary significance of the reduced morphology of the three additional species recognised here.